Yoga-Based Group Intervention for In-patients With Schizophrenia Spectrum Disorders—A Qualitative Approach - Schulze, Theresa; Hahn, Eric; Hahne, Inge; Bergmann, Niklas; Fuchs, Lukas Marian; Mähler, Franziska; Zierhut, Marco Matthäus; Ta, Thi Minh Tam; Pijnenborg, Gerdina Hendrika Maria; Böge, Kerem (Frontiers in Psychiatry, 2021)
Yoga may pose a promising complementary therapy in the multimodal treatment of in-patients with schizophrenia spectrum disorders (SSD). However, to date, no studies have qualitatively examined in-patients’ with SSD experiences of Yoga as well as their perceptions of its limitations and benefits as a treatment component. This qualitative study aimed to assess the mechanisms and processes of Yoga-based Group Intervention (YoGI) for in-patients with SSD by exploring their subjective experiences. Findings could serve as a preliminary basis for developing an effective and evidence-based YoGI manual tailored to this patient group. In total, 25 semi-structured interviews were conducted directly after YoGI, for which responses were either noted down by hand or audio-recorded. The interview guide was pilot-tested and consisted of fourteen questions to explore the personal articulated experiences of participation in YoGI from in-patients with SSD. Positive, negative, depressive, and anxiety symptoms were assessed during a diagnostic interview and through questionnaires. The interview data was transcribed, coded by two independent researchers, and analysed using an inductive thematic approach. The research team collaboratively discussed emerging categories to reduce redundancy and form meaningful themes and subthemes. The analysis revealed seven main themes. YoGI was perceived as feasible and focusing on individual adaptation, captured by the theme inclusivity. Nevertheless, participants encountered challenges; thus, physical limitations need to be considered. While practicing together, participants experienced interconnectedness and developed a mindful stance as they accepted their limitations and adapted exercises with self-compassion. Patients described that following the flow of the asanas required physical persistence, which ultimately led many participants to experience confidence and relaxation. YoGI affected symptom representation as heightened awareness led participants to notice impeding as well as improved symptoms. YoGI showed various promising effects on in-patients with SSD. Future research should examine to what extent these effects can be sustained and how the mindful approach during YoGI can be transferred to areas outside the Yoga class. Furthermore, a randomised controlled trial could investigate the effectiveness of a manualised YoGI.